2017
DOI: 10.1080/13854046.2017.1373859
|View full text |Cite
|
Sign up to set email alerts
|

The stakeholders’ project in neuropsychological report writing: a survey of neuropsychologists’ and referral sources’ views of neuropsychological reports

Abstract: The survey findings highlight the disjuncture between what neuropsychologists typically do in their practice of report writing versus what they believe is useful for patients and referral sources. The survey also highlights differences between writing practices of neuropsychologists and what referral sources identify as the most valuable aspects of reports to assist them in caring for their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…Results of several studies, especially qualitative comments from both parents and teachers, highlight the benefits of reports that are concise and have minimal jargon Cheung et al, 2014;Keenan et al, 2019;Postal et al, 2018;Stark et al, 2014). This observation is consistent with expert opinion about the disadvantages of lengthy, technical report-writing styles (Donders, 1999).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Results of several studies, especially qualitative comments from both parents and teachers, highlight the benefits of reports that are concise and have minimal jargon Cheung et al, 2014;Keenan et al, 2019;Postal et al, 2018;Stark et al, 2014). This observation is consistent with expert opinion about the disadvantages of lengthy, technical report-writing styles (Donders, 1999).…”
Section: Discussionsupporting
confidence: 70%
“…Referring provider satisfaction and related experiences. We analyzed data from the subset of Postal et al (2018) sample of referring providers who were primarily pediatric (n ¼ 129). Regarding which report sections are most valuable, respondents preferred the recommendations (65%) and diagnoses/impressions (64%).…”
Section: Correlates Of Parent Satisfaction and Related Experiencesmentioning
confidence: 99%
“…We can speculate that this advantage is of lesser priority to physicians who expect to answer a specific medical question, and it may lengthen the evaluation process as well as the final report. Indeed, physicians often express dissatisfaction from the length of reports and from the related slow turnaround [14]. Israeli practitioners shared these sentiments, and cited report length as the top disadvantage of NPA.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the neuropsychologist will consider qualitative aspects not typically captured by traditional scoring methods (i.e., the patient’s approach to a task). While complex and nuanced formulation of the neuropsychologist’s conclusions are important to document, a recent nationwide survey revealed that most referral sources pay the greatest attention to diagnosis and to recommendations ( Postal et al, 2018 ). Thus, there is a need for a simplified method to convey a concise summary of DBS screening related neuropsychological findings.…”
Section: Introductionmentioning
confidence: 99%